BEHIND THE KICK: UNDERSTANDING LOCAL FUTSAL SHOE CHOICES IN INDONESIA - A COMPREHENSIVE STUDY ON BRAND IMAGE, PRODUCT QUALITY, PRICE, AND CUSTOMER SATISFACTION - Mukhammad Khasbiyash Shiddiqi; Muchammad Saifuddin (PT. Mawadaku Sukses Solusindo, 2023)
This paper aims to evaluate the loyalty of Indonesian futsal players towards the Futsal Shoe product. The study investigates the effects of Brand Image, Product Quality, and Price on customer satisfaction and, subsequently, their loyalty. The research employs a quantitative approach, sourcing data from 210 participants. Statistical tests including path analysis, t-test, and Sobel test were utilized to validate hypotheses.The findings show that brand image, product quality, and price significantly influence customer satisfaction. Interestingly, while both brand image and product quality impact customer loyalty, price doesn't seem to have a direct influence on loyalty. However, the level of customer satisfaction was found to play a crucial role in driving customer loyalty. In conclusion, brand image, product quality, and price are important in shaping customer satisfaction with Futsal shoes, which in turn drives customer loyalty. The price, however, doesn't directly affect loyalty. Hence, the study recommends that companies should concentrate on enhancing brand image and product quality to boost customer satisfaction and loyalty.